2012
DOI: 10.1104/pp.112.204503
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of Strigolactone Signaling in Maize Architecture and the Uncoupling of a Branching-Specific Subnetwork      

Abstract: Strigolactones (SLs) control lateral branching in diverse species by regulating transcription factors orthologous to Teosinte branched1 (Tb1). In maize (Zea mays), however, selection for a strong central stalk during domestication is attributed primarily to the Tb1 locus, leaving the architectural roles of SLs unclear. To determine how this signaling network is altered in maize, we first examined effects of a knockout mutation in an essential SL biosynthetic gene that encodes CAROTENOID CLEAVAGE DIOXYGENASE8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
111
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 69 publications
11
111
1
Order By: Relevance
“…2) (Arite et al 2012;Guan et al 2012;Kretzschmar et al 2012). In support of the strigolactone-promoting primary root growth, Ruyter-Spira et al (2011) demonstrated that when grown without sucrose, GR24 applications trigger root growth in a MAX2-dependent manner.…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 94%
“…2) (Arite et al 2012;Guan et al 2012;Kretzschmar et al 2012). In support of the strigolactone-promoting primary root growth, Ruyter-Spira et al (2011) demonstrated that when grown without sucrose, GR24 applications trigger root growth in a MAX2-dependent manner.…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 94%
“…This transcription factor acts as a key integrator of several other pathways, such as the cytokinin pathway and the recently proposed sucrose signaling pathway in pea (Mason et al, 2014;Rameau et al, 2015). Interestingly, the maize ortholog (TB1) of the gene encoding this transcription factor seems to act independently of SLs to repress shoot branching (Guan et al, 2012). In rice, other transcription factors, such as MADS57 and IPA1/OsSPL14, that are involved in shoot branching have also been connected to key components of the SL signaling pathway, but whether these various transcription factors mediate SL signaling, and if or how they lie downstream of the D14-D3-D53 axis, are still not clear (Guo et al, 2013a;Lu et al, 2013).…”
Section: Models For Sl Signaling In the Control Of Shoot Branchingmentioning
confidence: 99%
“…Accordingly, SL-deficient mutants have a higher lateral root density . They also have a shorter primary root, not only in Arabidopsis, but also in rice and maize (Arite et al 2012;Guan et al 2012;Ruyter-Spira et al 2011). These phenotypes could only be rescued by the application of the synthetic SL analogue GR24 to the SL biosynthesis mutants, but not in those affected in signalling, indicating that SLs regulate root architecture in a MAX2-dependent manner Koltai et al 2010;MayzlishGati et al 2012;Ruyter-Spira et al 2011).…”
Section: Sls and Root System Architecturementioning
confidence: 99%